Endovascular Treatment of Patients with Popliteal Artery Aneurysms (a Literature Review) - S. A. Prozorov (Неотложная медицинская помощь, 2020)
The purpose of this review is to evaluate the results endovascular treatment of popliteal artery aneurysms. Endovascular treatment using stent grafts is a safe and effective alternative to open surgical repair, has a lower wound complication rate and shorter length of hospital stay, satisfactory technical and clinical results even at long-term follow-up. In patients requiring long segment coverage or numerous stents, the poor state of distal blood flow may increase the risk of failure. Careful patient selection, proper operative technique and adequate sizes of stent grafts are required for good outcomes.Author declare lack of the conflicts of interests.